An evaluation of purified Salmonella Typhi protein antigens for the serological diagnosis of acute typhoid fever. Issue 2 (August 2017) - Tran Vu Thieu, Nga; Trinh Van, Tan; Tran Tuan, Anh; Klemm, Elizabeth J.; Nguyen Ngoc Minh, Chau; Voong Vinh, Phat; Pham Thanh, Duy; Ho Ngoc Dan, Thanh; Pham Duc, Trung; Langat, Pinky; Martin, Laura B.; Galan, Jorge; et al.
Summary: Objectives: The diagnosis of typhoid fever is a challenge. Aiming to develop a typhoid diagnostic we measured antibody responses against Salmonella Typhi ( S . Typhi) protein antigens and the Vi polysaccharide in a cohort of Bangladeshi febrile patients. Methods: IgM against 12 purified antigens and the Vi polysaccharide was measured by ELISA in plasma from patients with confirmed typhoid fever (n = 32), other confirmed infections (n = 17), and healthy controls (n = 40). ELISAs with the most specific antigens were performed on plasma from 243 patients with undiagnosed febrile disease. Results: IgM against the S . Typhi protein antigens correlated with each other (rho > 0.8), but not against Vi (rho < 0.6). Typhoid patients exhibited higher IgM against 11/12 protein antigens and Vi than healthy controls and those with other infections. Vi, PilL, and CdtB exhibited the greatest sensitivity and specificity. Specificity and sensitivity was improved when Vi was combined with a protein antigen, generating sensitivities and specificities of 0.80 and >0.85, respectively. Applying a dynamic cut-off to patients with undiagnosed febrile disease suggested that 34–58% had an IgM response indicative of typhoid. Conclusions: We evaluated the diagnostic potential of several S . Typhi antigens; our assays give good sensitivity and specificity, but require further assessment in differing patient populations.